Implementation of Independent Character Strengthening Through Scout Extracurricular Activities Class VI at SDN Gelam 2 Candi : Implementation of Independent Character Strengthening Through Scout Extracurricular Activities Class VI at SDN Gelam 2 Candi - Fazira, Erra; Wahyuni, Akhtim (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe the implementation of scout extracurricular activities and to describe the strengthening of independent character in scouting activities. This study uses qualitative research methods that produce descriptive data in the form of written or spoken words from people and behaviors experienced by researchers. The subjects of this study were 4 grade VI students and grade VI scout coaches. in the field. The value of the Persami activity is that students are able to participate in these activities with enthusiasm and enthusiasm. The second is on the value of not depending on others, the value of being able to understand the material and complete assignments without bothering others, the value of confidence in completing assignments, students are also capable and finally the value of ability in making decisions students are also capable of this. Highlights: Active Participation: Scout activities foster enthusiasm and engagement among students, encouraging their active involvement in the extracurricular program. Development of Self-Reliance: Through assignments and tasks, students cultivate a sense of self-reliance, enhancing their ability to comprehend and complete tasks independently. Confidence and Decision-making: Participation in scouting builds students' confidence in task completion and decision-making skills, promoting their overall competence. Keywords: Scout Extracurricular Activities, Independent Character Strengthening, Student Enthusiasm, Self-Reliance